2015
DOI: 10.5937/industrija43-6677
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the performance of mutual funds: A case study

Abstract: In this paper we evaluate the performance of eight open-end mutual funds in the Republic of Serbia for the period 2009-2012, with the aim of testing the justification of active portfolio management of mutual funds, and determining the selection capability of Serbian portfolio managers. Riskweighted returns of mutual funds are compared with the risk-weighted return of the leading Belgrade Stock Exchange index, Belex15, whereas the following are used as performance measures: Sharpe ratio (), Treynor ratio (), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…the Sharpe, Treynor and Jensen ratios. Research using these indicators was carried out, among others, by Shukla and van Inwegen [1995], Kothari and Warner [2001], and Jakšić et al [2015]. Shukla and van Inwegen [1995] tried to answer the question whether local managers perform better than foreign ones.…”
Section: Review Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…the Sharpe, Treynor and Jensen ratios. Research using these indicators was carried out, among others, by Shukla and van Inwegen [1995], Kothari and Warner [2001], and Jakšić et al [2015]. Shukla and van Inwegen [1995] tried to answer the question whether local managers perform better than foreign ones.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…The results of the Fama-French model gave better results than those based on the CAPM model. Jakšić et al [2015] used the ratings of Sharpe, Treynor and Jensen to assess the mutual funds of the Serbian market in the period 2009-2012. The results obtained were worse than those that were set for the market portfolio.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…The vast majority of authors use the following ratios to evaluate the risk return profile of the investment: Sharpe ratio (Sharpe 1966), Jensen's alpha (Jensen 1968), Modigliani-Modigliani, standard deviation. To test the performance Jaksic, Lekovic and Milanovic (Jaksic et al 2015) used the Sharpe ratio, Treynor ratio, and Jensen's Alpha index. Researchers concluded that both the Sharpe and Treynor ratios, when analysed separately, did not represent significant results.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Performance evaluation of mutual funds, in this area, a number of studies conducted in all over the world, in finance it is a widely discussed issue and comprehensively examined in the developed capital market (Korkeamaki & Smythe, 2004;Kar & Shil, 2016;Soderlind, Dahlquist, & Engstrom, 2000). Friend, Brown, Herma, and Vickers (1962) were a first analysed the performance of mutual funds (Jaksic, Lekovic, & Milanovic, 2015;Redman, Gullet, & Manakyan, 2000). Markowitz (1952) set the portfolio selecting for investment in available securities and on beliefs about their future performances.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Laes and Silva's (2014) research on Brazil mutual funds' performance showed that the largest fund performs better than the small and middle-sized funds. Jaksic et al (2015) explored the performance of eight open-ended mutual funds in Serbia. The conclusion of their work is that the compared to the market portfolio Serbian mutual funds has low-grade performance because of domestic portfolio manager's lack of selection capabilities.…”
Section: Literature Reviewmentioning
confidence: 99%